The Opportunities and Challenges regarding Induced Platelets from Human Pluripotent Stem Cells - Meng-Xue Xu; Li-Ping Liu; Yu-Mei Li; Yun-Wen Zheng (Stem Cells International)
As a standard clinical treatment, platelet transfusion has been employed to prevent hemorrhage in patients with thrombocytopenia or platelet dysfunctions. Platelets also show therapeutic potential for aiding liver regeneration and bone healing and regeneration and for treating dermatological conditions. However, the supply of platelets rarely meets the rising clinical demand. Other issues, including short shelf life, strict storage temperature, and allogeneic immunity caused by frequent platelet transfusions, have become serious challenges that require the development of high-yielding alternative sources of platelets. Human pluripotent stem cells (hPSCs) are an unlimited substitution source for regenerative medicine, and patient-derived iPSCs can provide novel research models to explore the pathogenesis of some diseases. Many studies have focused on establishing and modifying protocols for generating functional induced platelets (iPlatelets) from hPSCs. To reach high efficiency production and eliminate the exogenous antigens, media supplements and matrix have been optimized. In addition, the introduction of some critical transgenes, such as c-MYC, BMI1, and BCL-XL, can also significantly increase hPSC-derived platelet production; however, this may pose some safety concerns. Furthermore, many novel culture systems have been developed to scale up the production of iPlatelets, including 2D flow systems, 3D rotary systems, and vertical reciprocal motion liquid culture bioreactors. The development of new gene-editing techniques, such as CRISPR/Cas9, can be used to solve allogeneic immunity of platelet transfusions by knocking out the expression of B2M. Additionally, the functions of iPlatelets were also evaluated from multiple aspects, including but not limited to morphology, structure, cytoskeletal organization, granule content, DNA content, and gene expression. Although the production and functions of iPlatelets are close to meeting clinical application requirements in both quantity and quality, there is still a long way to go for their large-scale production and clinical application. Here, we summarize the diverse methods of platelet production and update the progresses of iPlatelets. Furthermore, we highlight recent advances in our understanding of key transcription factors or molecules that determine the platelet differentiation direction.